2003
DOI: 10.1038/ng1223
|View full text |Cite
|
Sign up to set email alerts
|

LINE-mediated retrotransposition of marked Alu sequences

Abstract: Alu elements are the most successful transposons in humans. They are 300-bp non-coding sequences transcribed by RNA polymerase III (Pol III) and are expected to retrotranspose with the aid of reverse transcriptases of cellular origin. We previously showed that human LINEs can generate cDNA copies of any mRNA transcript by means of a retroposition process involving reverse transcription and integration by the LINE-encoded endonuclease and reverse transcriptase. Here we show mobility of marked Alu sequences in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
996
3
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 904 publications
(1,054 citation statements)
references
References 47 publications
18
996
3
3
Order By: Relevance
“…Alu elements might preferentially recognize the chromatin near housekeeping genes while LINE-1 elements and other long transposons avoid such chromatin. However, the notion of strikingly distinct insertion biases seems contrary to the finding that the LINE-1 transposition machinery mobilizes both LINE-1 and Alu elements (Jurka, 1997;Dewannieux et al, 2003) which consequently insert at the same consensus TT/AAAA sequence (Feng et al, 1996;Jurka, 1997;Cost and Boeke, 1998). Indeed, the factor IX gene has been shown to be targeted by one disease-causing LINE-1 insertion and two independent Alu insertions (Ostertag and Kazazian, 2001) suggesting that Alu and LINE-1 elements can share an insertion hotspot.…”
Section: The Possibility That Non-random Insertion Patterns Contributmentioning
confidence: 86%
See 1 more Smart Citation
“…Alu elements might preferentially recognize the chromatin near housekeeping genes while LINE-1 elements and other long transposons avoid such chromatin. However, the notion of strikingly distinct insertion biases seems contrary to the finding that the LINE-1 transposition machinery mobilizes both LINE-1 and Alu elements (Jurka, 1997;Dewannieux et al, 2003) which consequently insert at the same consensus TT/AAAA sequence (Feng et al, 1996;Jurka, 1997;Cost and Boeke, 1998). Indeed, the factor IX gene has been shown to be targeted by one disease-causing LINE-1 insertion and two independent Alu insertions (Ostertag and Kazazian, 2001) suggesting that Alu and LINE-1 elements can share an insertion hotspot.…”
Section: The Possibility That Non-random Insertion Patterns Contributmentioning
confidence: 86%
“…The non-LTR retrotransposons consist primarily of the Long Interspersed Nuclear Element-1 (LINE-1, 15.6%) and the nonautonomous Alu element (10.1%). LINE-1 transposons encode the enzymatic activities required for both their own mobility and for the mobilization of Alu elements (Hagan and Rudin, 2002;Kajikawa and Okada, 2002;Dewannieux et al, 2003). Alu transposons differ from other SINEs in that they are not derived from tRNA genes, but rather from the 7SL RNA gene (Ullu and Tschudi, 1984;Quentin, 1994;Smit, 1996;Okada and Hamada, 1997;Terai et al, 1998;Lander et al, 2001) which encodes the RNA component of the signal recognition particle that mediates the translocation of nascent secretory and membrane proteins (Wild et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Retrotransposition-competent cell lines have greatly assisted in understanding the mechanism of non-LTR retrotransposition in vivo [6][7][8][9][10] . Here we report the first such system in a parasitic protist E. histolytica.…”
Section: Discussionmentioning
confidence: 99%
“…Although sequence analysis of human Alu subfamilies showed the existence of mosaic elements 29, these were not experimentally found [7][8][9] . Mosaics could have been missed in these studies because of the smaller number of retrotransposition events scored, and the selection pressure used.…”
Section: Mismatchesmentioning
confidence: 99%
“…Alu elements amplified via RNA intermediates by a mechanism of retrotransposition that is currently under investigation. As they do not encode any protein, their amplification has probably been dependent on the transposition machinery of other retrotransposing elements, and it has recently been shown that they could use LINE-1 elements for this purpose [4]. Very few Alu elements are able to retrotranspose; they emerged from a limited number of loci that are considered as master genes of Alu amplification.…”
Section: Introductionmentioning
confidence: 99%